Wealth Metaphors in Morgan Housel’s The Psychology of Money Introduction Section - Dyta Septiyatik (Humanitatis : Journal of Language and Literature, 2023)
This study aims to identify wealth metaphors in Morgan Housel’s The Psychology of Money introduction section. Conceptual metaphor is a concept of an abstract entity drawn in that of a concrete concept to provide a better understanding (Lakoff & Johnson, 1980). Moreover, metaphors are used widely in human everyday life, for instance in movies, literary works, and even small talk. The data were collected utilizing a corpus-based method with the help of tools including WordNet, TRIPS Word Lookup, and AntConc. To analyze the data, the relevance theory by Carston was used in determining metaphorical expression (Carston, 2011) from wealth-related utterances. Additionally, the source domains and the mappings were executed by looking into the co-text of each metaphorical expression. Finally, the wealth metaphors were concluded according to the mappings. The study result shows thirty-six metaphorical expressions found in the introduction section of The Psychology of Money, which were subsequently categorized into smaller groups constructing five wealth metaphors. The source domains are laboratory, school, competition, euphoria, and nature, with wealth as the target domain. To end with, it is recommended that further researchers dig deeper into conceptual metaphors of crucial aspects of human life through a complete work beyond the book’s introduction.